Mekanisme Pasar Islami Dalam Konteks Idealita dan Realita (Studi Analisis Pemikiran Al-Ghazali dan Ibnu Taimiyah) - Irawan, Mul (Departemen Ekonomi Syariah Fakultas Ekonomi dan Bisnis Universitas Airlangga, 2015)
This paper discusses the Islamic market mechanism in terms of the thought of Al-Ghazali (1058-1111 AD) and Ibn Taymiyyah (1263-1328 AD). Their thought constitute intellectual treasures were very helpful in finding idealistic notions, as well as to becoming a contemporary Islamic economic thought. Al-Ghazali and Ibn Taymiyyah thoughts in relation to the Islamic market mechanisms has enriched Islamic economics with a wider range for the conceptualization and application. In the context of idealita, Islamic market mechanisms can generate a fair price for producers and consumers, as long as the market mechanisms work perfectly. It became the correction solution-on the realities of the present market mechanisms are still many colored fraud and injustice.Â Keyword :Â Islamic market mechanism, idealistic, realistic